Drawing on Dialogues in Arts-Based Dynamic Interpersonal Therapy (ADIT) for Complex Depression: A Complex Intervention Development Study Using the Medical Research Council (UK) Phased Guidance - Havsteen-Franklin, Dominik; Oley, Mary; Sellors, Sarah Jane; Eagles, Diane (Frontiers in Psychology, 2021)
This study describes the work of an art psychotherapy clinician-researcher group in psychiatry using a phased practice-based evidence method to develop a model of arts-based dynamic interpersonal therapy (ADIT) to treat complex depression. The study focuses on people referred to mental health services who present with symptoms of complex depression. The psychobiological aetiology of depression offers evidence that the physiology and psychology of the person should be taken into account when providing psychological treatment. For example, evidence suggests complex depression is associated with a range of physical illnesses within a relational context, including the progression of chronic physical conditions, and therefore this study considered the interoceptive and physically active use of art making as an important component to the intervention. Given the paucity of evidence-based treatments for complex depressive disorders, the complex epidemiology and the socioeconomic burden, it is becoming increasingly important that treatment is offered that is accessible, acceptable and effective to treat complex depression. This study used the Medical Research Council (MRC) phased intervention development protocol. The focus is on the assimilation of structural elements (phases and foci of treatment) of Dynamic Interpersonal Therapy (DIT) with psychodynamic art psychotherapy practice. Art psychotherapy has been used effectively for complex psychiatric presentations and has been widely used for depression since the introduction of DIT into primary care contexts and the workforce regulation of increased access to psychological therapies (NHS England » Workforce, 2020.). The findings from this study indicate that the protocol for arts-based dynamic interpersonal therapy can be clearly defined using the Medical Research Council’s phased approach to intervention development. The results show that the theory inherent to dynamic art psychotherapy practice is comparable with verbal interventions, and the results of the pilot indicated good outcomes and high levels of acceptability amongst referrers. The findings from this study indicate that the protocol is clearly defined and comparable with verbal interventions and the results of the pilot indicated good outcomes and high levels of acceptability amongst professionals, including referrers and arts psychotherapists.